2020
DOI: 10.1108/er-07-2020-0343
|View full text |Cite
|
Sign up to set email alerts
|

Employee happiness and corporate social responsibility: the role of organizational culture

Abstract: PurposeThis research explores how does the organizational culture influence internal corporate social responsibility (CSR) actions and the effect of these actions on the level of happiness of employees.Design/methodology/approachThe study adopts an employee perspective since the perception of employees is the unit of analysis. By relying on a sample of 921 workers of firms from different sectors and sizes headquartered in Spain, the empirical analysis is performed using partial least squares.FindingsThe findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 67 publications
0
42
0
Order By: Relevance
“…Regarding the methodological implications, and according to the reviewed articles in the present paper, it appears that future research would highly benefit from employing ethnographic methods [61], longitudinal studies [59,88,94,98], comparative and crosscultural research [67,80,83,85], experimental research design [57], and data collecting from different sources [84,87], specifically relying more on the employees rather than senior managers' perspectives [47,48]. However, these methodological recommendations mostly come from those quantitative studies that originated from utilitarian philosophies.…”
Section: Implications For Context and Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Regarding the methodological implications, and according to the reviewed articles in the present paper, it appears that future research would highly benefit from employing ethnographic methods [61], longitudinal studies [59,88,94,98], comparative and crosscultural research [67,80,83,85], experimental research design [57], and data collecting from different sources [84,87], specifically relying more on the employees rather than senior managers' perspectives [47,48]. However, these methodological recommendations mostly come from those quantitative studies that originated from utilitarian philosophies.…”
Section: Implications For Context and Methodsmentioning
confidence: 95%
“…Although all the reviewed papers assert that CSR firm policies impact SRHRM practices, some studies also explored other drivers within firms that might have been influential in this regard. Such factors include firms' strategic policies and priorities [48,60], available financial resources [60], HRM systems design [60], HRM power in the organization [26], ethics-oriented HRM philosophies [65], the multi-nationality of firms [93], as well as organizational structure and culture [80]. The third antecedent category is related to the individual factors, including employees' needs and wants [21,62,77,79], the presence of an ethical leader [60,61,75,89,92,101], the HR professionals' perception of their ethical role [61], and the role of employees' representatives in organizations [56].…”
Section: Antecedents Of Srhrmmentioning
confidence: 99%
“…The main agenda of employee-level CSR activities is to focus on the wellbeing of the workers through responsible business operations [42]. Through CSR activities, a socially responsible enterprise seeks to develop a partnership with its employees to create better opportunities and convert the workplace into a place where employees happily perform their job [43]. Various research studies have reported on the positive link between CSR and economic performance [44][45][46].…”
Section: Csr and Economic Performancementioning
confidence: 99%
“…The remaining 13 factors were collectively referred to as 'Internal Organization Development'. It has conclusively been shown that the organization's internal development is critical to the turnover rate, happiness, job satisfaction, and burnout of medical personnel [53][54][55].…”
Section: Sense Of Gain and Internal Organization Developmentmentioning
confidence: 99%